Dominasi Bayani dalam Pembelajaran PAI: Analisis Epistemologi Muhammad Abed Al-Jabiri dan Implikasinya terhadap Pendidikan Islam - Anis Ulfatul Kamilah; Mamluk Nurul Wada’ah; Maimun (Kartika: Jurnal Studi Keislaman, 2026)
Islamic Religious Education (PAI) plays an important role in shaping students' religious understanding, character, and spirituality. However, PAI learning practices tend to be dominated by bayani reasoning, which emphasizes textual authority, memorization of arguments, and normative approaches, potentially limiting the development of students' critical thinking skills and religious reflection. This study aims to analyze the forms of bayani reasoning dominance in PAI learning based on Muhammad Abed Al-Jabiri's epistemological perspective and examine its implications for Islamic education. This research employs a qualitative approach with library research type. Data were obtained from Al-Jabiri's works as primary sources and various relevant literature as secondary sources. Data analysis used content analysis technique by examining the concepts of bayani, burhani, and irfani. The results show that PAI subjects such as Fiqh, Qur'anic Hadith, Akidah Akhlak, and Islamic Cultural History are still dominated by bayani epistemology. Therefore, balanced integration with burhani and irfani epistemology is needed. The implications of this study emphasize the importance of curriculum reconstruction, transformation of teacher roles, diversification of learning methods, and expansion of learning outcome orientations holistically